Prinsip-Prinsip dalam Belajar: Implementasi dan Tantangan di Era Modern - luthfi luthfi; Nurfarida Deliani; Juliana Batubara (JDP (JURNAL DINAMIKA PENDIDIKAN), 2026)
Learning principles are the fundamental foundation of an effective learning process. This article examines the implementation of learning principles in the context of contemporary learning, identifies the challenges faced, and explores the Qur'anic perspective on learning. Using a literature review approach, this article analyzes how the principles of readiness, motivation, activity, and individualization can be applied in facing learning challenges in the digital era. The results show that although the implementation of learning principles faces various obstacles such as limited resources and digital divides, adaptive solutions through technology optimization, collaborative learning, and sustainable professional development can improve learning effectiveness. The integration of the spiritual values of the Qur'an also provides a holistic dimension that enriches the educational process. This article provides practical recommendations for educators, policymakers, and other education stakeholders.